The power of incumbent political capital of Suharsono-Halim in the 2020 Bantul Regional Head Election - Hendy Setiawan; Kelik Iswandi (Masyarakat, Kebudayaan dan Politik, 2022)
The regional head election in Bantul in 2020 is an interesting political contestation event. This is because the previous incumbent regent and deputy regent in Bantul participated in this political contest, which broke up the joint venture. The struggle for power in Bantul is interestingly won by the previous deputy regent, Abdul Halim Muslih. This victory certainly raises a big question as to why Suharsono, who is actually an incumbent regent, is easily defeated. In fact, under the leadership of Suharsono, Bantul has always made various achievements both locally, nationally and internationally. Departing from this problem, it is necessary to examine how the strength of the political modalities between the two was so that in the end Abdul Halim Muslih won. The research conducted by qualitative approach by using descriptive method. The research materials were collected from library research. The author collects data through literature studies, both journals, media, news, KPU documents, or other literature that supports this paper. The researchers argue that the incumbent Abdul Halim Muslih’s victory in the 2020 Bantul Regional Head Election cannot be separated from the strength of social, cultural, and political modalities. The advantage of this modality is able to gain votes in the 2020 Bantul Regional Head Election. Although it must be admitted that Suharsono’s economic modality is better than Abdul Halim Muslih.